A new construction of switched reluctance motor improving magnetic field energy and torque production - (:unkn) unknown (WORLD SCIENTIFIC AND ENGINEERING ACAD AND SOC, 2007)
This paper is performed to develop a new 8-6 pole switched reluctance motor (SRM) in order to improve the magnetic field energy and torque production; and describes the differences of standart 8/6-pole SRM and that newly developed SRM in dynamic characteristics such as magnetic field energy and torque production. Finite element analysis (FEA) was used to obtain the nonlinear magnetisation data for application to the modelling. As known; finite element method (FEM) has been a powerful tool to solve many complex problems in electromagnetics. For the optimum design of switched reluctance motors, this paper presents the methods and results, which are calculated by the finite element analysis. Thus; it has been possible to determine the effects of different construction methods and motor specifications on the performance. The comparison of the dynamic output performance for each motor provides the basis for the discussion on the relationship of output performance of switched reluctance motor to its physical size [2], construction and excitation method. In this paper; by using FEM, we are going to develop a model of SR motor that is different from the ones developed before, and try to explain the running discriminations between the developed and the known SRMs.
Keywords: finite elements; magnetic field energy; torque production; switched reluctance